2021
DOI: 10.3390/pathophysiology28010012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aqueous Extract of Lycopersicum esculentum L. var. “Camone” Tomato on Blood Pressure, Behavior and Brain Susceptibility to Oxidative Stress in Spontaneously Hypertensive Rats

Abstract: Behavioral disorders affect millions of people worldwide. Hypertension contributes to both the development and progression of brain damage and cognitive dysfunction and could represent the most powerful modifiable risk factor for cerebral vessel dysfunction and consequent behavioral impairment. Tomato contains antioxidants and bioactive molecules that might play an important role in the prevention of cardiovascular and brain diseases. The effects of the combined gel and serum from Lycopersicum esculentum L. va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Angiotensin II (Ang II) can be used to induce hypertension in rats, as it activates both NADPH and NADH oxidase. It is no effect in rats with normal blood pressure [40]. These findings support the antihypertensive capacity of lycopene without causing hypotension.…”
Section: Lycopene and Blood Pressuresupporting
confidence: 74%
See 1 more Smart Citation
“…Angiotensin II (Ang II) can be used to induce hypertension in rats, as it activates both NADPH and NADH oxidase. It is no effect in rats with normal blood pressure [40]. These findings support the antihypertensive capacity of lycopene without causing hypotension.…”
Section: Lycopene and Blood Pressuresupporting
confidence: 74%
“…indicated that treating hypertensive rats with an aqueous extract of tomatoes or captopril for four weeks both led to an outstanding decrease in blood pressure [40].…”
Section: Lycopene and Blood Pressurementioning
confidence: 99%
“…The authors suggested that the consumption of tomato-based diets has the potential to reduce plasma cholesterol in humans, an aspect that merits study. In a related study, Frosini et al [36] reported that treating hypertensive rats with tomato gel/serum for four weeks caused a significant reduction in blood pressure, decreased locomotor activity, and grooming behavior. Tomatine alone was ineffective in reducing blood pressure but did affect the other two parameters.…”
Section: Preventive Effects Against Hyperlipidemia Atherosclerosis Ob...mentioning
confidence: 99%